2019
DOI: 10.1016/j.tranpol.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the sustainability of national logistics performance using Data Envelopment Analysis

Abstract: Supplier selection has become one of the most crucial tasks in supply chain management, especially in the procurement function. In recent years, the importance of selecting the best possible suppliers has been enhanced due to the emergence of sustainability issues. Manufacturers have been obliged and/or encouraged by various stakeholders to embed environmental and social concerns into their supply chain activities. As a consequence of this evolution, procurement managers have started to not only evaluate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 154 publications
0
100
0
3
Order By: Relevance
“…Considering the goal of the article, it was assumed that the level of logistics safety would be measured by the performance logistics index (customs, infrastructure, international shipments, logistics quality and competence, tracking and trading, timeliness), and the effectiveness of the systems, resulting from their safety management, by gross operating rate (in %) and turnover per person employed (in thousand euro) for the transport and storage sector, because of the sector's integrating and coordinating function in the realization of logistics processes. Enterprises in this sector are considered to be the basis of the logistics industry, which plays a major role in the global business environment because time and costs are significant to the success of a supply chain (Rashidi, Cullinane, 2019). The impact of logistics efficiency factors on the effects of logistics system safety management will be determined on the basis of the regression model.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the goal of the article, it was assumed that the level of logistics safety would be measured by the performance logistics index (customs, infrastructure, international shipments, logistics quality and competence, tracking and trading, timeliness), and the effectiveness of the systems, resulting from their safety management, by gross operating rate (in %) and turnover per person employed (in thousand euro) for the transport and storage sector, because of the sector's integrating and coordinating function in the realization of logistics processes. Enterprises in this sector are considered to be the basis of the logistics industry, which plays a major role in the global business environment because time and costs are significant to the success of a supply chain (Rashidi, Cullinane, 2019). The impact of logistics efficiency factors on the effects of logistics system safety management will be determined on the basis of the regression model.…”
Section: Methodsmentioning
confidence: 99%
“…Social and environmental activities play a more important role in promoting sustainable logistics than financial-economic activities [60]. Rashidi and Cullinane [61] found that the national logistics industry with high SEE index has the following features: (i) well-planned logistics network infrastructure; (ii) high quality of service operators; (iii) shipments tracing technology; and (iv) efficient timetable scheduling.…”
Section: Evaluation On the Social Environmental And Economic Impactsmentioning
confidence: 99%
“…Research using the DEA method to obtain the level of efficiency in the field of transportation has been widely carried out abroad. G. Georgiadis, I. Politis, and P. Papaioannou, has conducted research on the measurement and improvement of efficiency and effectiveness of the public bus transportation system in Greece [6]; Marchetti and Wanke have conducted research related to the analysis of the efficiency of cargo train transportation in Brazil [7]; Rashidi and Cullinane evaluated the performance of sustainable national logistics for 22 countries from the Organization for Economic Cooperation and Development (OECD) [8].…”
Section: Efficiency Of Transportation Researchmentioning
confidence: 99%